RESEARCH ON THE STATE OF RAILWAY INFRASTRUCTURE PROVISION - Малішевська, Аліна; Тройнікова, Олена (SWorldJournal, 2025)
Railway transport is of strategic importance for the country’s economy. The article examines the current state of railway infrastructure, analyzes the sources of ensuring the restoration and repair of railway track infrastructure